Liquidity Risk Measurement for Mutual Funds Investing in Less-Liquid Assets - Van Horne, Richard H. (Miary oceny ryzyka płynności funduszy inwestycyjnych. Zastosowanie modelu korelacji z procesem AR(1) oraz modelu z efektami opóźnionymi, 2016)
I apply two models from the existing academic literature to assess liquidity risk in groups of mutual funds as well as in individual high yield mutual funds. These models are a serial correlation model with an AR(1) process and a lagged effects model. These models were most recently applied in the field of hedge fund research to measure liquidity risk and to evaluate the performance of aggregated groups of hedge funds, organized by investment strategy. I apply these models in the recently developing area of liquid alternative mutual funds and at the level of the individual mutual fund. A perceived benefit to investors in the liquid alternative funds is the structural, daily-redemption liquidity of the fund shares. Yet, the liquidity of the underlying securities portfolios held by these funds is not apparent to the investors and may expose the investor to heightened liquidity risk. The models perform well and will be applied to identify liquidity risk in a further ongoing study of the performance and liquidity of individual mutual funds. Liquidity risk assessment should play a vital role in performance evaluation and fund selection
Nauki o Finansach = Financial Sciences, 2016, Nr 2 (27), s. 65-79
Keywords: liquidity risk; mutual funds; serial correlation; lagged effects; ryzyko płynności; fundusz inwestycyjny; model korelacji z procesem AR(1); model z efektami opóźnionymi